The global profile of antibiotic resistance in bacteria isolated from goats and sheep: a systematic review - Herawati, Okti; Bejo, Siti Khairani; Zakaria, Zunita; Ramanoon, Siti Zubaidah (Veterinary World, 2023)
Background and Aim: Antibiotic resistance has become an issue of global importance due to increasing levels of bacterial infections worldwide. Farm management and usage of antibiotics in livestock are known risk factors associated with the increase in global levels of antibiotic resistance. Goats and sheep are examples of livestock with large populations. Although antibiotic resistance in bacteria from livestock negatively affects both human health and the economy, the global data regarding this issue in goats and sheep are limited. Therefore, this study aimed to provide information on the antibioticresistance profile of bacteria isolated from goats and sheep worldwide (Asia, Europe, and Africa). Materials and Methods: We performed a systematic review of articles published on this topic without any restriction on the year of publication. We searched the Directory of Open Access Journals, PubMed, Google Scholar, and Scopus using Boolean logic through various keywords. The search generated a total of 1325 articles, and after screening for duplicates and implementing inclusion and exclusion criteria, qualitative synthesis (i.e., qualitative systematic review) was performed on 37 articles. Results: The synthesized information indicated that 18 Gram-positive and 13 Gram-negative bacterial species from goats and sheep were resistant to ten antibiotics, namely penicillin, ampicillin, amoxicillin, chloramphenicol, streptomycin, tetracycline, cephalothin, gentamicin, ciprofloxacin (CIP), and sulfamethoxazole. The prevalence of antibiotic resistance ranged from 0.4 to 100. However, up to 100 of some bacteria, namely, Salmonella Dublin, Aeromonas caviae, and Aeromonas sobria, were susceptible to CIP. Staphylococcus aureus and Escherichia coli were highly resistant to all antibiotics tested. Moreover, eight of the ten antibiotics tested were critically important antibiotics for humans. Conclusion: Antibiotic-resistant bacteria in goats and sheep are a potential risk to animal and human health. Collaboration between all stakeholders and further research is needed to prevent the negative impacts of antibiotic resistance.